2021
DOI: 10.1249/mss.0000000000002823
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age and Estradiol on Sympathetic Nerve Activity Responses to Exercise in Women

Abstract: Introduction: Postmenopausal women (PMW) display exaggerated increases in blood pressure (BP) during exercise, yet the mechanism(s) involved remain unclear. Moreover, research on the impact of menopausal changes in estradiol on cardiovascular control during exercise are limited. Herein, we tested the hypothesis that sympathetic responses during exercise are augmented in PMWcompared with young women (YW), and estradiol administration attenuates these responses. Methods: Muscle sympathetic nerve activity (MSNA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…It has been suggested that the absolute (rather than the percentage) ΔMSNA exerts the most influence on target organ responses, and is therefore the most physiologically significant measure (Tanaka et al, 1999). All recent studies (Badrov et al, 2016;Gagnon et al, 2015;Lee et al, 2021;Miller et al, 2019;Notarius et al, 2019;Wenner et al, 2022), with the exception of Keller-Ross et al (2020), that compared MSNA responses to acute physiological stressors (i.e., handgrip exercise and cold pressings) between younger and older individuals reported absolute MSNA changes only. MSNA BF is related to the plasma noradrenaline concentration (Morlin et al, 1983;Ng et al, 1993;Wallin et al, 1987) and renal noradrenaline spillover (Wallin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the absolute (rather than the percentage) ΔMSNA exerts the most influence on target organ responses, and is therefore the most physiologically significant measure (Tanaka et al, 1999). All recent studies (Badrov et al, 2016;Gagnon et al, 2015;Lee et al, 2021;Miller et al, 2019;Notarius et al, 2019;Wenner et al, 2022), with the exception of Keller-Ross et al (2020), that compared MSNA responses to acute physiological stressors (i.e., handgrip exercise and cold pressings) between younger and older individuals reported absolute MSNA changes only. MSNA BF is related to the plasma noradrenaline concentration (Morlin et al, 1983;Ng et al, 1993;Wallin et al, 1987) and renal noradrenaline spillover (Wallin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Only males were included in the present study. Several age‐related alterations may preferentially increase the likelihood of an exaggerated ABP response to exercise in females compared with males (Trinity et al., 2018; Wenner et al., 2022). Older females exhibit impaired vasodilatory capacity during exercise (Parker et al., 2008, 2010), and changes in MSNA (Matsukawa et al., 1998) and vascular dysfunction (Celermajer et al., 1994) are accelerated in postmenopausal females compared with age‐matched males.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in primarily male samples, either no impact of age (Greaney et al., 2013) or attenuated (Houssiere et al., 2006; Markel et al., 2003; Ng et al., 1994) sympathetic and pressor responses to exercise and PECO are reported in older adults. Conversely, post‐menopausal females demonstrate exaggerated increases in MSNA and BP during isometric exercise and PECO compared with young, pre‐menopausal females, likely due to the loss of oestradiol following menopause (Wenner et al., 2022). Taken together, these data suggest that there may be a sex‐specific impact of age on the sympathetic neurocirculatory responses to exercise and PECO.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired FMD and increased sympathetic activity are associated with the increased risk of incident hypertension in healthy postmenopausal women [ 13 , 14 ]. Our participants had a normal or elevated SBP at rest.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction precedes the development of arterial stiffness [ 12 ] and hypertension in healthy postmenopausal women [ 13 ]. Another mechanism for hypertension in postmenopausal women is elevated sympathetic activity [ 14 ]. Systolic hypertension and consequent heart failure with preserved ejection fraction are highly prevalent in older women due to increased aortic stiffness [ 15 ] and sympathetic-mediated vasoconstriction [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%